Influence of Breed and Genotype on the Onset and Distribution of Infectivity and Disease-associated Prion Protein in Sheep Following Oral Infection with the Bovine Spongiform Encephalopathy Agent. Issue 1 (January 2015) - McGovern, G.; Martin, S.; Jeffrey, M.; Bellworthy, S.J.; Spiropoulos, J.; Green, R.; Lockey, R.; Vickery, C.M.; Thurston, L.; Dexter, G.; Hawkins, S.A.C.; González, L.
Summary: The onset and distribution of infectivity and disease-specific prion protein (PrP d ) accumulation was studied in Romney and Suffolk sheep of the ARQ/ARQ, ARQ/ARR and ARR/ARR prion protein gene ( Prnp ) genotypes (where A stands for alanine, R for arginine and Q for glutamine at codons 136, 154 and 171 of PrP), following experimental oral infection with cattle-derived bovine spongiform encephalopathy (BSE) agent. Groups of sheep were killed at regular intervals and a wide range of tissues taken for mouse bioassay or immunohistochemistry (IHC), or both. Bioassay results for infectivity were mostly coincident with those of PrP d detection by IHC both in terms of tissues and time post infection. Neither PrP d nor infectivity was detected in any tissues of BSE-dosed ARQ/ARR or ARR/ARR sheep or of undosed controls. Moreover, four ARQ/ARQ Suffolk sheep, which were methionine (M)/threonine heterozygous at codon 112 of the Prnp gene, did not show any biological or immunohistochemical evidence of infection, while those homozygous for methionine (MARQ/MARQ) did. In MARQ/MARQ sheep of both breeds, initial PrP d accumulation was identified in lymphoreticular system (LRS) tissues followed by the central nervous system (CNS) and enteric nervous system (ENS) and finally by the autonomic nervous system and peripheral nervous system and other organs. Detection of infectivity closely mimicked this sequence. No PrP d was observed in the ENS prior to its accumulation in the CNS, suggesting that ENS involvement occurred simultaneously to that of, or followed centrifugal spread from, the CNS. The distribution of PrP d within the ENS further suggested a progressive spread from the ileal plexus to other ENS segments via neuronal connections of the gut wall. Differences between the two breeds were noted in terms of involvement of LRS and ENS tissues, with Romney sheep showing a more delayed and less consistent PrP d accumulation than Suffolk sheep in such tissues. Whether this accounted for the slight delay (∼5 months) in the appearance of clinical signs in Romney sheep is debatable since by the last scheduled kill before animals reached clinical end point, both breeds showed widespread accumulation and similar magnitudes of PrP d accumulation in the brain.